The effect of demöoperidone on gallbladder and sphincter of oddi motility in human - Ender ELLİDOKUZ and Ethem TANKURT and Berna DEĞİRMENCİ and Enis İĞCİ and Hatice DURAK and Ömür GÖNEN (Turkish Journal of Gastroenterology, 2019)
-